The differential of the student inserted in the experience of pet-saúde: monitors' experience report (International Seven Journal of Multidisciplinary, 2023)
The Education through Work for Health Program - PET / Saúde implements a fine line, in accordance withinter professionality, with full emphasis on the family health strategy, so that its members have a wide experience about the professional activities present in the group. It also provides na opportunity to improve interprofessional work in the service and academic learning, according to SUS needs. The study is an experience report and aimed to portray the full experience of the monitors of the PET-Saúde Interprofessional of Cesmac. Regarding the analysis of literature, it was observed that extracurricular activities have gained a lot of visibility among students, however, there is a scar city of studies on this topic in Brazil. Since the first experience lived at PET, he strives to always show dynamic and team work, instigating the critical and research sense of themonitors. However, it is noted the importance of na interprofessional team and the involvement in the participation of Pet-Saúde that allows the academic to learn from work and experience the natural reality of the health system. The monitors refer to brief reports throughout the article, highlighting their main experiences and points of view, in which, during the period of the experience, a commitment to team work was noticed, instigating the critical sense and research of the monitors. In addition to practical experiences carried out in a sequence of planning, execution and evaluation of all proposed actions, with a focus on community satisfaction. DOI: 10.56238/isevmjv2n1-003